2017
DOI: 10.1016/j.jacc.2017.04.056
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Experience for Transcatheter Aortic Valve Replacement and Relation to Outcomes

Abstract: The initial adoption of TAVR into practice in the United States showed that increasing experience was associated with better outcomes. This association, whether deemed a prolonged learning curve or a manifestation of a volume-outcome relationship, suggested that concentrating experience in higher volume heart valve centers might be a means of improving outcomes. (STS/ACC Transcatheter Valve Therapy Registry [TVT Registry]; NCT01737528).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
0
5

Year Published

2018
2018
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 236 publications
(109 citation statements)
references
References 24 publications
4
100
0
5
Order By: Relevance
“…Carroll et al reported the learning curve associated with TAVR from the STS/ACC registry. According to the study, there was a linear association, meaning better outcomes with increased hospital volume for in‐hospital mortality, vascular complications, and bleeding events.…”
Section: Discussionmentioning
confidence: 99%
“…Carroll et al reported the learning curve associated with TAVR from the STS/ACC registry. According to the study, there was a linear association, meaning better outcomes with increased hospital volume for in‐hospital mortality, vascular complications, and bleeding events.…”
Section: Discussionmentioning
confidence: 99%
“…One study compared procedure volume to adverse events. More volume was associated with less adverse outcomes including vascular complications and bleeding (22). This is an interesting look at prevention and argues for more specialized sites with high volume, allowing cardiologists to further perfect their techniques.…”
Section: Prevention Of Access Site Complicationsmentioning
confidence: 95%
“…Lower in‐hospital risk‐adjusted outcomes such as mortality, bleeding, and vascular complications (but not stroke) were seen when site volume increased. In a volume‐outcome model, from the first case to 400th case, adjusted mortality (4–2%), bleeding (10–5%), vascular complications (6–4%), and stroke (2–1.6%) decreased significantly . “Public health discussions regarding hospital volumes required for starting or maintaining TAVR programs often stoke an impassioned debate: should we limit TAVR to high volume hospitals; or, should we allow TAVR at smaller hospitals to enhance patient access to a life‐saving treatment?”…”
Section: Risk Predictors and Specific Prognostic Markersmentioning
confidence: 99%